2012
DOI: 10.1002/marc.201200525
|View full text |Cite
|
Sign up to set email alerts
|

Anion Responsive Imidazolium‐Based Polymers

Abstract: Stimuli responsiveness in polymer design is providing basis for diversely new and advanced materials that exhibit switchable porosity in membranes and coatings, switchable particle formation and thermodynamically stable nanoparticle dispersions, polymers that provide directed mechanical stress in response to intensive fields, and switchable compatibility of nanomaterials in changing environments. The incorporation of ionic liquid monomers has resulted in many new polymers based on the imidazolium group. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
86
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(88 citation statements)
references
References 91 publications
2
86
0
Order By: Relevance
“…Thee lectronic and optical properties of these efficient metal-free photocatalysts can be tuned by molecular design, copolymerization, doping, texture or morphology engineering,a nd surface heterojunctions. [12] Here,w er eport the design and synthesis of watercompatible conjugated nanoparticles and porous polymers bearing imidazolium-based ionic-liquid (IL) units [13] as highly efficient metal-free visible-light photocatalysts in aqueous environment. [6] Some research activities showed their applications for molecular oxygen activation, [7] hydroxylation of arylboronic acids, [8] dehalogenation reaction [9] visible-light photoinitiation for free radical polymerization, [10] and hydrogen evolution.…”
supporting
confidence: 89%
“…Thee lectronic and optical properties of these efficient metal-free photocatalysts can be tuned by molecular design, copolymerization, doping, texture or morphology engineering,a nd surface heterojunctions. [12] Here,w er eport the design and synthesis of watercompatible conjugated nanoparticles and porous polymers bearing imidazolium-based ionic-liquid (IL) units [13] as highly efficient metal-free visible-light photocatalysts in aqueous environment. [6] Some research activities showed their applications for molecular oxygen activation, [7] hydroxylation of arylboronic acids, [8] dehalogenation reaction [9] visible-light photoinitiation for free radical polymerization, [10] and hydrogen evolution.…”
supporting
confidence: 89%
“…Connectivity to water is also provided by imidazolium or imidazolium bromide. Any particular anion chosen to pair with an imidazolium group controls solubility of such a pair in water, and bromide provides a hydrophilic pairing (Texter, ). The NL of this study has been found to be hydrogels and are highly suitable for coupling disperse phases to aqueous continuous phases.…”
Section: Resultsmentioning
confidence: 99%
“…Over the recent years, many PIL-structures have been synthesized and they have found potential applications in many fields, such as polymer electrolytes, carbon precursors, and fuel cell membranes [1e3]. A characteristic feature of PILs is their counter ion responsiveness [4]. The choice of counter ion influences many properties of the PILs such as solubility, glass transition temperature and thermal stability [5e9].…”
Section: Introductionmentioning
confidence: 99%